Kamus Bahasa Mandarin di Yogyakarta - Frida Anis Handayani; Eritrina Putri Ekantari (JLA (Jurnal Lingua Applicata), 2019)
The Mandarin language has complex linguistic rules that not everyone isn't able to arrange a good Mandarin dictionary. The writer of Mandarin dictionary should have an abundant knowledge and experience in this language, so they can develop high-quality Mandarin dictionary which is easy to be understood by the reader. This article explains some examples of errors found in several Mandarin language dictionaries with a lexicology and lexicographic approach. The conclusion of this article is that not all dictionaries on the market are high quality, for example in the writing of hanzi, pinyin, and sentences. Mandarin language learners must be selective when they want to buy a dictionary, the quality of a dictionary depends on the writer, accuracy and printing.